1997
DOI: 10.1021/jp970097k
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Enhanced Raman Spectroscopy of Phosphate Anions:  Adsorption on Silver, Gold, and Copper Electrodes

Abstract: The adsorption of phosphate anions on Ag, Au, and Cu electrodes from H2O and D2O solutions has been studied by means of surface-enhanced Raman spectroscopy (SERS). The interpretation of the spectra based on the solution Raman data and frequency shifts upon solution H2O/D2O exchange are presented. The prominent band at 1070−1100 cm-1, observed from adsorbed PO4 3- and HPO4 2- ions, exhibits downshifts of about 10 cm-1 in D2O solutions and has been assigned to the asymmetric P−O stretching mode. The correspondin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
127
2

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(142 citation statements)
references
References 44 publications
13
127
2
Order By: Relevance
“…This structure is well known from other studies of [19]. These studies also revealed a strong dependence of the appar- copper surface under low potential condition [13].…”
Section: Stm Measurementssupporting
confidence: 82%
See 1 more Smart Citation
“…This structure is well known from other studies of [19]. These studies also revealed a strong dependence of the appar- copper surface under low potential condition [13].…”
Section: Stm Measurementssupporting
confidence: 82%
“…A previous SERS study [13] it appears reasonable to assign the anodic peak at −250 mV to the adsorption of phosphate anions from the neutral phosphate buffer solution used in the present study. Consequently, the three cathodic peaks appearing close to the onset of the HER correspond to the phosphate desorption.…”
supporting
confidence: 58%
“…Also possible is an enhancement of Raman lines by attachment of phosphate on the surface of cell fragments. [15] Related XAFS studies of U VI [12] and Pu VI [10] precipitated with NaH 2 PO 4 at pH 4.5 confirmed that the precipitate is UO 2 (H 2 PO 4 ) 2 . These data, combined with the fluorescence and Raman spectra, lead to the conclusion that bacterial decomposition released H 2 PO 4 À that complexed the uranyl and formed a precipitate of UO 2 (H 2 PO 4 ) 2 if the solubility product of this species was exceeded.…”
mentioning
confidence: 81%
“…Two methods that are suitable www.chemeurj.org for studying interfacial processes of selected metal ions on cell surfaces are time-resolved laser-induced fluorescence spectroscopy (TRLFS) [6,14] and surface-enhanced or resonance Raman spectroscopy. [15,16] TRLFS can detect changes in the chemical environment of fluorescing actinides through changes in their fluorescence spectra. U VI , for example, has excellent fluorescence properties.…”
Section: Introductionmentioning
confidence: 99%
“…However, even the simplest phosphate-buffered solutions (PBS), commonly used for analysis of biological species, tend to foul Au electrodes as a consequence of phosphate anion adsorption on their surface [7][8][9].…”
Section: Introductionmentioning
confidence: 99%